MANAJEMEN PEMBIAYAAN DALAM PENINGKATAN PRESTASI PESERTA DIDIK - ., Iratnawati (Inspiratif Pendidikan, 2019)
In everyday terms, the term finance or financing comes from the word finance associated with efforts to obtain or raise capital to finance activities that will be carried out. But lately, the notion of finance or capital has been expanded, not only as an effort to raise capital, but also to include the dimensions of capital use. The expansion of understanding is a result of the awareness that capital is a scarce production factor so it needs to be used as well as possible. Education funding as stated in the National Education Standards: Government Regulation No.19 of 2005 consists of 3 major parts, namely: First, investment costs include the costs of providing facilities and infrastructure, human resource development and permanent working capital. Second, operational costs include education costs that must be spent by students to be able to follow the learning process regularly and continuously. Third, personal costs.